(untitled) (Journal of Rangpur Medical College, 2023)
Background: Epilepsy is a medical condition that requires long-term treatment with antiepileptic drugs. Different epidemiological studies revealed an increased risk of atherogenic cardiovascular diseases in patients under antiepileptic therapy. The possible etiologic suggestion is alterations of the serum homocysteine, folate, and vitamin B12 metabolism. Objective: To evaluate serum homocysteine, folate, and vitamin B12 level in patients under antiepileptic monotherapy. Methods: This cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College from July 2017 to June 2018 through purposive sampling. In this study, forty diagnosed patients under antiepileptic monotherapy and forty age and sex-matched apparently healthy control were selected according to selection criteria, from OPD of the Neurology department, Dhaka medical college hospital. Results: In patients under antiepileptic therapy, mean (±SD) of serum homocysteine (μmol/L), folate (ng/ml), and vitamin B12 (pg/ml) were 14.15±3.4, 13.61±2.02, 361.78±41.26 respectively. In the healthy control group, serum homocysteine (μmol/L), folate (ng/ml), and vitamin B12 (pg/ml) were 8.78±2.59, 16.71±2.06 and 366.69±44.15 respectively. Serum homocysteine level was found higher and folate level was found lower in patients with antiepileptic therapy which were statistically significant (p<0.001). But serum B12 level difference was found statistically non-significant. Serum homocysteine level has a positive correlation (p-value 0.001, r value 0.71) and serum folate has a negative correlation (p-value 0.001, r value -0.65) with the duration of antiepileptic therapy. Conclusion: A higher level of serum homocysteine and a lower level of folate was found in patients under antiepileptic therapy. But there was no significant change in the serum vitamin B12 level of these patients. J Rang Med Col. March 2023; Vol. 8, No. 2:44-48